2014
DOI: 10.1021/ac404072z
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Sensitive Phosphorescent Nanomaterials Produced from High-Density Polyethylene Films by Local Solvent-Crazing

Abstract: Discrete solid-state phosphorescent oxygen sensors produced by local solvent-crazing of high density polyethylene films are described. The simple spotting of dye solution followed by tensile drawing of the polymer substrate provides uniform nanostructures with good spatial control, effective encapsulation of dye molecules, and quenchability by O2. The dye-polymer composite sensors prepared using toluene as a solvent and stabilized by annealing at high temperature, show moderate optical signals, near-optimal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…Therefore, polymer crazing in liquid media may be considered as a http://dx.doi.org/10.1016/j.eurpolymj.2015.03.003 0014-3057/Ó 2015 Elsevier Ltd. All rights reserved. method for obtaining nanoporous materials (membranes and sorbents) and as a process for producing nanocomposites and highly disperse polymer-polymer blends [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polymer crazing in liquid media may be considered as a http://dx.doi.org/10.1016/j.eurpolymj.2015.03.003 0014-3057/Ó 2015 Elsevier Ltd. All rights reserved. method for obtaining nanoporous materials (membranes and sorbents) and as a process for producing nanocomposites and highly disperse polymer-polymer blends [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to much better BS compared to conventional indicators the new dyes proved to be promising for application in planar optodes and fiber-optic sensors (mainly based on polystyrene and its derivatives). These sensors were used for measurement of oxygen solubility in organic solvents [55], online measurement of antioxidant activity using a capillary-based sensor coupled to an HPLC system [56], imaging of oxygen dynamics of symbiotic cyanobacterium Prochloron [57], luminescence imaging of physiological wound oxygenation [58], ultrafast measurement of oxygen flux with fiber-optic microsensors [59], preparation of structured materials for food packaging applications [60]. In vitro experiments using simulated subcutaneous read-out demonstrated superiority of the new sensors over those based on UV–vis indicators which were found to be virtually useless due to the dramatic signal loss [54].…”
Section: Oxygen Probes and Sensorsmentioning
confidence: 99%
“…To be usable and viable in large scale applications such as food packaging, O 2 sensors should be simple, scalable, reproducible, stable and cost less than 1 cent each [17]. We have recently reported that non-woven polyolefin fabric materials (polypropylene (PP) and polyethylene (PE) based), as well as poly(phenylene sulphide) films (PPS) can be used as simple polymer host and support materials, which allow fabrication of simple and robust O 2 sensors by solvent crazing [18,19] and polymer swelling [20] methods. These food-compatible polymer materials possess many desirable qualities, such as gas permeability, process ability, simple composition and uniformity, storage stability and low cost.…”
Section: Introductionmentioning
confidence: 99%